2007
DOI: 10.1111/j.1572-0241.2006.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events as a Risk Factor for Inflammatory Bowel Disease Onset: A Population-Based Case–Control Study

Abstract: Despite its separate association with CD, LE occurrence does not appear to be an independent risk factor for IBD onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 34 publications
1
55
0
2
Order By: Relevance
“…The relationship between abuse and IBS also declined when controlling for adult SES and life stressors. In our study and in other studies, life stress (Aggarwal et al, 2006;Locke, Weaver, Melton, & Talley, 2004), SES (Lerebours et al, 2007), and marital status (Andrews et al, 2005) were significantly associated with IBS. Our study and Henningsen et al's (2003) meta-analysis indicated that FSS are related to but not fully dependent on depression and anxiety.…”
Section: Different Relationships Between Physical Abuse and Each Fsssupporting
confidence: 49%
“…The relationship between abuse and IBS also declined when controlling for adult SES and life stressors. In our study and in other studies, life stress (Aggarwal et al, 2006;Locke, Weaver, Melton, & Talley, 2004), SES (Lerebours et al, 2007), and marital status (Andrews et al, 2005) were significantly associated with IBS. Our study and Henningsen et al's (2003) meta-analysis indicated that FSS are related to but not fully dependent on depression and anxiety.…”
Section: Different Relationships Between Physical Abuse and Each Fsssupporting
confidence: 49%
“…The increased prevalence of depression and anxiety observed among patients with IBD 1,2 has led to suggestions that the co-existence of mood disorders may influence the natural history, [3][4][5] although whether this affects the development of disease is less certain. 6,7 In IBD, psychological co-morbidity, including anxiety, depression, somatisation, and perceived stress, is not only associated with active disease, but also ongoing symptoms in the absence of inflammation. [8][9][10][11][12] Although a temporal relationship between the presence of psychological co-morbidity and the onset of IBD activity has been suggested, 13 a causal relationship remains unproven.…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments, colitis can be exacerbated by early life stress (neonatal maternal deprivation) in genetically susceptible IL-10 KO mice, but not in wild type mice, probably through impaired intestinal barrier function [178]. Although most patients consider stressful life events important in the development of their disease, one study focusing on life events occurring no more than six months prior to the onset of diagnosis failed to find any correlation in UC patients compared to controls [179]. In CD patients, life events occured more frequently in the past 6 month preceding diagnosis, however, the association was no more significant when other factors were also taken into account.…”
Section: Stress and Mood Disordersmentioning
confidence: 99%